L1‎‎ Norm Based Data Analysis and Related Methods: (1632-1989) - Bidabad, Bijan (Australian Finance & Banking Review, 2019)
This paper gives a rather general view on the L1‎‎ norm criterion on the area of data analysis and related topics. We tried to cover all aspects of mathematical properties, historical development, computational algorithms, simultaneous equations estimation, statistical modeling, and application of the L1‎‎ norm in different fields of sciences.